"PhD, meet QPR": The quality in postgraduate research conference and the development of doctoral education. Issue 1 (11th May 2015) - McCulloch, Alistair; Picard, Michelle Yvette
Abstract : Purpose: – The purpose of this paper is to provide an overview of the relationship between the quality in postgraduate research conference (QPR) and the developing doctoral education agenda, as well as serving as an introduction to this special edition of the International Journal for Researcher Development . Design/methodology/approach: – The paper adopts a conceptual and rhetorical approach. Findings: – The paper argues that, over its two decades of existence, the QPR conference has been at the forefront of developments in doctoral education and has also influenced practice and policy in the area. Originality/value: – The paper is the first to review the QPR conference and its place in the development of doctoral education.